Histopathological effects of ethyl 2-cyanoacrylate tissue adhesive following surgical application: an experimental study - BOZKURT, SÜHEYLA (OXFORD UNIV PRESS INC, 2004)
Objective: To investigate experimentally the possible histopathological effects of ethyl 2-cyanoacrylate glue when used as a tissue adhesive in cardiovascular and thoracic surgery. Methods: Sprague-Dawley rats were used for this study. For histopathological investigation, a study group of 144 rats in which intentionally produced lesions in myocardium (n = 36), ascending aorta (n = 36), lung (n = 36) and abdominal aorta (n = 36) were closed by using ethyl 2-cyanoacrylate was compared with the control group (n = 144) in which the same lesions were closed by using sutures. On each of days 1, 7, 15, 30, 45 and 60, six rats from the study group and six rats from the control group were sacrificed and analyzed for each relevant organ in terms of bonding of ethyl 2-cyanoacrylate polymers to tissue, foreign body reaction, inflammatory reactions, and necrosis. Endothelial cell damage, intimal hyperplasia, and thrombus formation were also evaluated in arteriotomy sections. Results: In histopathological analysis of vascular, myocardial and pulmonary tissue sections, there was no significant histopathological difference between conventionally sutured tissues and ethyl 2-cyanoacrylate-applied tissues. Conclusions: As no significant difference between conventional suture and ethyl 2-cyanoacrylate application was detected in terms of histopathological reactions, ethyl 2-cyanoacrylate may be considered as an alternative or adjunct to conventional techniques in controlling hemorrhage that cannot be controlled by conventional methods, in tissue repair and in the control of pulmonary air leakage, and may be used in vascular, myocardial and pulmonary surgery. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: cardiovascular surgery; thoracic surgery; ethyl 2-cyanoacrylate; tissue adhesive; histopathological effects; RUPTURE; REPAIR; PATCH